2023
DOI: 10.3390/genes14010133
|View full text |Cite
|
Sign up to set email alerts
|

High Coverage Mitogenomes and Y-Chromosomal Typing Reveal Ancient Lineages in the Modern-Day Székely Population in Romania

Abstract: Here we present 115 whole mitogenomes and 92 Y-chromosomal Short Tandem Repeat (STR) and Single Nucleotide Polymorphism (SNP) profiles from a Hungarian ethnic group, the Székelys (in Romanian: Secuii, in German: Sekler), living in southeast Transylvania (Romania). The Székelys can be traced back to the 12th century in the region, and numerous scientific theories exist as to their origin. We carefully selected sample providers that had local ancestors inhabiting small villages in the area of Odorheiu Secuiesc/S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 65 publications
1
12
0
Order By: Relevance
“…The genomic results largely correspond with earlier uniparental marker studies (Maróti et al 2022;. Some mtDNA data have also been published from the Hungarian conquerors or contemporary Hungarian speakers (Borbély et al 2023;Tömöry et al 2007;Neparáczki, Juhász, et al 2017;Brandstätter et al 2007; Maár et al 2021). These mtDNA studies of early and present-day Hungarians revealed a diverse composition of maternal haplogroups with ca 25-30% Easter-Eursian components in the ancient datasets, with marking dilution up to present day (Neparáczki, Juhász, et al 2017;Brandstätter et al 2007möry et al 2007Bogácsi-Szabó et al 2005).…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…The genomic results largely correspond with earlier uniparental marker studies (Maróti et al 2022;. Some mtDNA data have also been published from the Hungarian conquerors or contemporary Hungarian speakers (Borbély et al 2023;Tömöry et al 2007;Neparáczki, Juhász, et al 2017;Brandstätter et al 2007; Maár et al 2021). These mtDNA studies of early and present-day Hungarians revealed a diverse composition of maternal haplogroups with ca 25-30% Easter-Eursian components in the ancient datasets, with marking dilution up to present day (Neparáczki, Juhász, et al 2017;Brandstätter et al 2007möry et al 2007Bogácsi-Szabó et al 2005).…”
Section: Introductionsupporting
confidence: 82%
“…Mitogenome sequences from Hungarian populations from Hungary, Székely (Hungarian) people from Transylvania near Odorheiu Secuiesc, Romania(Borbély et al 2023) the here presented two populations from Baranja and Zobor region were tested in Arlequin for population differentiation and showed F ST values below 0.0035 with signi cant p-values.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Genetic data focusing on uniparental markers -speci cally Y-STR (short tandem repeat) and Y-SNP (single nucleotide polymorphism) -from modern Hungarian-speaking populations are available in the literature [21][22][23][24][25][26][27] . This includes data from groups residing in geographically secluded regions within the Carpathian Basin, like Bodrogköz 25 , as well as the Rétköz and Váh valley communities 26 .…”
Section: Introductionmentioning
confidence: 99%
“…The genomic results largely correspond with earlier uniparental marker studies 15,31 . Some mtDNA data have also been published from the Hungarian conquerors and contemporary Hungarian speakers 7,12,27,35,36 . These mtDNA studies of early and present-day Hungarians revealed a diverse composition of maternal haplogroups with ca 25-30% Easter-Eurasian components in the ancient datasets, with marking dilution up to present day 12,[35][36][37] .…”
Section: Introductionmentioning
confidence: 99%